Analysis of the survival and clinical characteristics of colorectal cancer patients with mental disorders. Issue 3 (25th January 2021) - Kurashige, Junji; Iwatsuki, Masaaki; Mima, Kosuke; Nomoto, Daichi; Shigaki, Hironobu; Yamashita, Kohei; Morinaga, Takeshi; Iwagami, Shiro; Miyanari, Nobutomo; Baba, Hideo
Abstract: Aim: Many studies have shown that patients with mental disorders are less likely than non‐psychiatric patients to be diagnosed with or treated for various types of cancers because of their low awareness and understanding of the disease as well as reduced ability to cooperate with medical staff. We analyzed the clinical features of patients with colorectal cancer (CRC) and preexisting mental illness. Methods: All patients underwent primary tumor resection for CRC. We reviewed the records of 68 patients who were diagnosed with mental disorders. The patients' clinicopathological information was compared with that of a control group of 893 CRC patients. Results: There was no significant difference in the overall disease stage at the time of surgery between the groups. However, disease‐free survival, cancer‐specific survival, and overall survival were significantly worse in the mental disorder group than in the control group ( P  < .01). In particular, among those with stage III CRC, overall survival was significantly worse in the patients with mental disorders than in the non‐psychiatric patients ( P  < .001). The frequency of complications of ≥grade 2 according to the Clavien‐Dindo classification was higher in the SMI group because of postoperative paralytic ileus. Conclusions: Advanced CRC patients with mental disorders are less likely to receive postoperative adjuvant chemotherapy or treatment for recurrent cancer than CRC patients without mental disorders; therefore, they experience worse outcomes. Collaboration across multiple departments is necessary for managing CRC patients with mental disorders. Abstract : Patients with mental disorders exhibited significantly worse prognoses in terms of DFS, CSS, and OS than the patients in the control group.